Emerging Web Services Technology Volume III - Binder, Walter; Dustdar, Schahram; SpringerLink (Online service) (Basel : Birkhäuser Basel, 2010)
This book contains a collection of selected and revised papers originally presented at the Workshop on Emerging Web Service Technology (WEWST'08) held in conjunction with the 6th European Conference on Web Services (ECOWS'08) in November 2008 in Dublin, Ireland. Acting as an extension to the ECOWS conference, the main goal of the WEWST workshop is serving as a forum for providing early exposure and much needed feedback to grow and establish original and emerging ideas within the Web Services community. The wide variety of tools, techniques, and technological solutions presented in WEWST share one common feature: they advance the current Web Services research in new directions by introducing new and sometimes controversial ideas into the field.
Enforcing Advance Reservations for E-Science Workflows in Service Oriented Architectures -- Towards Reuse of Business Processes Patterns to Design Services -- Server-side Exception Handling by Composite Web Services -- A Mediator-Based Approach to Resolving Interface Heterogeneity of Web Services -- Efficient QoS-aware Service Composition -- A Distributed Service Component Framework for Interoperable and Modular Service-Oriented Pervasive Computing Applications -- Service Contract Compliance Management in Business Process Management -- An Architecture for Autonomic Web Service Process Planning -- Towards Service Architectures in Service-oriented Computing -- A Service Architecture Solution for Mobile Enterprise Resources: A Case Study in the Banking Industry -- Bringing Agility to Business Process Management: Rules Deployment in an SOA -- Architecting a Business Process Versioning Middleware for a Major Telecommunications Company.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Information systems; Information Systems; Computer Science; Information Systems Applications (incl.Internet).; Computer Communication Networks; Computer Systems Organization and Communication Networks; Management of Computing and Information Systems